The Role of Princess Ubolratana Rajakanya to Enhance Peaceful Society According to Sangahavatthu 4 - Sriboonpeng, Sarinee; Bannaruji, Banjob; Wattanapradith, Khantong (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This thesis, a qualitative-research form done by the tool of documentary study, is of 3 objectives: (1) to study Sangahavatthu 4 in Buddhist Scripture, (2) to study the history and the work performance of Princess Ubolratana Rajakanya, and (3) to analytically study the role of Princess Ubolratana Rajakanya to enhance peaceful society according to Sangahavatthu 4. From the research, it is found the followings: 1) Sangahavatthu 4 is the conducting and practice in living together in the society yielding sharing, love, unity and harmonization arisen from giving both materials and wisdom; it is with the know how to talk nicely, gently, properly to situations, the thinking of the benefits of all, and the proper behavior. 2) Princess Ubolratana Rajakanya Siriwattnapannavadi is knowledgeable and talent in many ways. The princess supports many activities that create love and unity of the national people, sees to her citizen’s sufferings and happiness; the Princess is a good role model and emphasizes on the welfare of her citizen as well. 3) Princess Ubolratana Rajakanya Siriwattnapannavadi arranges for project proceedings for happiness of the society in terms of donating both materials and Dhamma; the Princess has been a model of using polite words which is done for love, unity and loving-kindness. The Princess devotes and sacrifices both of her body and private properties in helping the citizen; the Princess reaches people without being pompous. The performing outcome of the Royal Initiative Project has been in accordance with Sangahavatthu 4 which brings a good role model to the society and enhances peace to all citizenry.